Exploring the properties and extraction of neem leaves - Shrinkhala Rai (International Journal of Toxins and Toxics, 2024)
Neem (Azadirachta indica) is a versatile medicinal plant, for its diverse therapeutic properties. This abstract provides a comprehensive overview of recent research focusing on phytochemical analysis, biochemical characterization, and antimicrobial susceptibility testing of Neem extracts. Utilizing the different from of chemical used in it, phytochemical analysis identified a plethora of secondary metabolites within Neem, including alkaloids, flavonoids, terpenoids, steroids, saponin, tannins, quinone, and phenolic compounds, indicative of its complex chemical composition. These bioactive constituents contribute significantly to Neem's pharmacological effects, highlighting its potential as a valuable natural remedy in healthcare. Biochemical analysis further elucidated Neem's enzymatic activities, particularly its antioxidant potential. Various enzymes involved in antioxidant pathways were identified, emphasizing Neem's ability to combat oxidative stress-related disorders and promote overall health and well-being through its antioxidant properties. Antimicrobial susceptibility testing demonstrated the potent efficacy of Neem extracts against a broad spectrum of pathogens, including bacteria, fungi, and parasites. Neem's antimicrobial activity can be attributed to its diverse bioactive constituents, which exhibit inhibitory effects on microbial growth and proliferation. These findings underscore Neem's potential as a natural alternative for antimicrobial therapy, offering promising avenues for the treatment and prevention of infectious diseases. In conclusion, this abstract underscore the importance of Neem in modern pharmacology, highlighting its phytochemical diversity, biochemical attributes, and potent antimicrobial properties. The results emphasize the need for further research and exploration of Neem's therapeutic potential in healthcare and pharmaceutical industries, paving the way for the development of novel Neem-based therapeutics.
Keywords: Azadirachta indica; Neem; antimicrobial susceptibility testing; biochemical characterization; medicinal plant; natural remedies; pharmacology; phytochemical analysis; therapeutic potential